Oil pipelines and public policy : analysis of proposals for industry reform and reorganization - Mitchell, Edward J.; American Enterprise Institute for Public Policy Research (Washington : American Enterprise Institute for Public Policy Research, 1979)
This is the proceedings of a conference sponsored by the American Enterprise Institute for Public Policy Research.The text represents the state of the debate in 1979 as it dealt extensively on the issue of profitability of pipelines , the case of divestiture among others.
Includes bibliographical references.
kjo 16/01/2019
Loans
Keywords: Petroleum pipelines; Pipelines; Public policy; Pipelines - economic aspects